IGF-I Exerts an Anti-inflammatory Effect on Skeletal Muscle Cells through Down-regulation of TLR4 Signaling - Lee, Won Jun (The Korean Association of Immunologists, 2011)
Although exercise-induced growth factors such as Insulin-like growth factor-I (IGF-I) are known to affect various aspects of physiology in skeletal muscle cells, the molecular mechanism by which IGF-I modulates anti-inflammatory effects in these cells is presently unknown. Here, we showed that IGF-I stimulation suppresses the expression of toll-like receptor 4 (TLR4), a key innate immune receptor. A pharmacological inhibitor study further showed that PI3K/Akt signaling pathway is required for IGF-I-mediated negative regulation of TLR4 expression. Furthermore, IGF-I treatment reduced the expression of various NF-κB-target genes such as TNF-α and IL-6. Taken together, these findings indicate that the anti-inflammatory effect of exercise may be due, at least in part, to IGF-I-induced suppression of TLR4 and subsequent downregulation of the TLR4-dependent inflammatory signaling pathway.